Ileus Obstruksi Parsial akibat Intususepsi Ileocaecal dan Tumor Colon Ascendens pada Pasien Perempuan Dewasa - Wijaya, Jefri (Jurnal Kedokteran Meditek, 2025)
Introduction: Intussusception is a rare condition in adults. It can cause ischemic necrosis, perforation, and peritonitis. Objective: This case report highlights the clinical presentation, diagnosis, and management of bowel obstruction due to intussusception in an adult. Case Illustration: A 43-year-old female patient presented with watery stools mixed with blackish blood, abdominal pain, vomiting, and decreased appetite. Abdominal examination revealed mild distension, reduced bowel sounds, generalized tenderness, and a firm, mobile mass (10 × 10 × 5 cm) in the right lower quadrant. Digital rectal examination showed a dilated rectal ampulla, extra luminal protrusion, and blackish blood-stained feces. Imaging studies confirmed a high-level obstruction and ileocecal intussusception with bowel wall edema. The patient was diagnosed with partial bowel obstruction. Discussion: This unusual case involves a localized tumor in the ascending colon acting as a lead point, leading to ischemia and mucosal necrosis. Accurate diagnosis in adults relies on timely imaging examinations. While plain radiography (BNO) may show signs of intestinal obstruction, its sensitivity is limited. Initial management focuses on stabilizing the patient’s condition by using a gastric tube for decompression, providing intravenous fluids for rehydration, administering analgesics and antibiotics, and, if appropriate, performing a barium or air enema to help reposition the affected segment. Prompt management is essential to prevent serious complications. Conclusion: Adult intussusception is rare and requires diagnosis through history, physical examination, and radiologic studies. Management involves initial medical stabilization and surgical intervention.